Stand-alone lumbar cage subsidence: A biomechanical sensitivity study of cage design and placement. (August 2018) - Calvo-Echenique, Andrea; Cegoñino, José; Chueca, Raúl; Pérez-del Palomar, Amaya
Highlights: A 3D lumbar functional spinal unit finite element model was created and a parametric model of an interbody cage was designed. A Drucker–Prager Cap plasticity formulation was used to predict plastic strains and bone failure in the vertebrae. The most influential parameters on the functional spinal unit biomechanics were size, curvature and cage placement. Wider cages and a more anteriorly placement would increase the volume of failed bone and, therefore, the risk of subsidence. This model provides a tool for the preoperative evaluation of the surgery outcome. Abstract: Background and objective: Spinal degeneration and instability are commonly treated with interbody fusion cages either alone or supplemented with posterior instrumentation with the aim to immobilise the segment and restore intervertebral height. The purpose of this work is to establish a tool which may help to understand the effects of intervertebral cage design and placement on the biomechanical response of a patient-specific model to help reducing post-surgical complications such as subsidence and segment instability. Methods: A 3D lumbar functional spinal unit (FSU) finite element model was created and a parametric model of an interbody cage was designed and introduced in the FSU. A Drucker–Prager Cap plasticity formulation was used to predict plastic strains and bone failure in the vertebrae. The effect of varying cage size, cross-sectional area, apparent stiffness and positioning was evaluated under 500 N preload followed by 7.5 Nm multidirectional rotation and the results were compared with the intact model. Results: The most influential cage parameters on the FSU were size, curvature congruence with the endplates and cage placement. Segmental stiffness was higher when increasing the cross-sectional cage area in all loading directions and when the cage was anteriorly placed in all directions but extension. In general, the facet joint forces were reduced by increasing segmental stiffness. However, these forces were higher than in the intact model in most of the cases due to the displacement of the instantaneous centre of rotation. The highest plastic deformations took place at the caudal vertebra under flexion and increased for cages with greater stiffness. Thus, wider cages and a more anteriorly placement would increase the volume of failed bone and, therefore, the risk of subsidence. Conclusions: Cage geometry plays a crucial role in the success of lumbar surgery. General considerations such as larger cages may be applied as a guideline, but parameters such as curvature or cage placement should be determined for each specific patient. This model provides a proof-of-concept of a tool for the preoperative evaluation of lumbar surgical outcomes.